Producción de textos escritos en inglés en estudiantes de segundo grado de secundaria en instituciones educativas de la zona urbana de San Juan Bautista según tipo de gestión 2021 - Bardales Manihuari, Gina Paola (2022)
This research objective was to compare second year students’ writing skills in English at public and private secondary schools in the urban area of Saint John district. The research was comparative type with field study, transactional contemporary and univariate designs. The study population was made up by 1546 students, with a probabilistic stratified with proportional allocation sample of 308. A valid and reliable writing performance test and a rubric were used as data gathering tools. Results show that the mean score in English writing was 5.79 for public schools and 6.02 out of 20 for private schools. Similarly, the results of the dimensions were: Adequacy of the text to the communicative situation (5.29 < 5.86), organization and development of ideas (5.71 < 5.91), Use of written language conventions (7.33 < 6.73). It was concluded that there were significant differences in writing skills performance between public and private school students as p-value = 0.025 < ? = 0.05, accepting the working hypothesis.